Nilai Produksi dan Pemasaran Gurita (Octopus sp) di Tiga Bersaudara Kabupaten Simeulue Provinsi Aceh - Ermiati Putri; Syarifah Zuraidah (Jurusan Sosial Ekonomi Perikanan, 2022)
Simeulue Regency has very diverse and abundant marine fishery resources, one of which is octopus (Octopus sp) which is a superior commodity that can improve the community's economy. This research was carried out in Tiga Bersaudara from August 30 to October 30, 2021. This study aims to determine the production and marketing value of octopus in the Tiga Bersaudara. In this study using qualitative data methods where this data can be more likely to explore problems more clearly because the research was carried out directly which was used in research. Based on the results of the research, the production of octopus in August and October increased while in September it decreased due to unfavorable weather factors. Advantages in the Tiga Bersaudara are good at implementing planning, organizing, directing and supervising. Where the quality of the octopus produced is maintained so that it can produce packaged products that can increase productivity.